Immunomodulatory and regenerative potential of mesenchymal stem cells in recurrent aphthous stomatitis: A narrative review - Vemilia Pasha Hawini; Iswerya Bala Subramaniam; Andari Sarasati; Fatma Yasmin Mahdani; Reiska Kumala Bakti; Diah Savitri Ernawati; Faezah Binti Rokhan (Faculty of Dental Medicine Universitas Airlangga, 2026)
Background: Recurrent Aphthous Stomatitis (RAS) is a chronic inflammatory disorder of the oral mucosa characterized by recurrent, painful ulcerations with an etiology that is not yet fully understood. Immunological, genetic, and environmental factors play significant roles in its pathogenesis. Conventional therapies, such as topical corticosteroids, antiseptics, and anti-inflammatory agents, are primarily symptomatic, providing temporary relief from pain and inflammation without addressing the underlying immune dysregulation or promoting mucosal regeneration. These limitations have led to increasing interest in novel therapeutic approaches, including Mesenchymal Stem Cell (MSC)–based therapy, which offers potential immunomodulatory and regenerative effects. Purpose: This narrative review aims to integrate and discuss the existing evidence regarding the immunomodulatory and tissue-repair roles of mesenchymal stem cells (MSCs) in recurrent aphthous stomatitis (RAS), with a focus on underlying biological mechanisms and current research gaps. Review: The current literature indicates that MSC-mediated immunomodulation in RAS is primarily inferred from preclinical models, in which reductions in pro-inflammatory cytokines and increased secretion of growth factors have been observed. Although these findings support a mechanistic rationale for MSC involvement in epithelial repair, direct and consistent evidence of ulcer healing and inflammation resolution remains limited. Translational application of these findings is constrained by heterogeneity in experimental designs and a lack of well-controlled clinical studies. Conclusion: RAS remains a chronic inflammatory condition without a definitive curative treatment. MSC-based therapies demonstrate promising dual immunomodulatory and regenerative potential; however, further clinical studies are required to establish safety, optimal delivery methods, and long-term efficacy.